ASSOCIATION BETWEEN SOME RISK FACTORS AND PROSTATE CANCER PROGRESSIONIN BASRAH, IRAQ - Rasha A. Al-Badran; Adnan Issa Al-Badran; Majed Azkar; Loma Al-Mansouri (Basrah Journal of Veterinary Research)
Prostate cancer is a complex disease in which both genetic and environmental influencesled to the development and growth of tumors. at the recent time, is considered the second mostcommon malignancy after lung cancer in men and the sixth leading cause of cancer – relateddeath worldwide.Sixty-seven blood samples of prostate cancer patients collected from Basrahoncology and Hematology center aging between (45-90). On the other hand, seventy bloodsamples of men without cancer were collected as control group aging between (45-90). Two mlof peripheral blood were drawn by sterilized syringe from the two groups than kept in the EDTAtube for DNA extraction for molecular study (not included). Both study groups have answeredquestions about personal information such as age, address, cigarette smoking, occupation, andfamily history.The present study found evidence that the aging was a significant risk factor fordeveloping prostate cancer, as well as family history increased the risk of disease abouteighteenfold (OR=18.8).Type of work people do related to the development of prostate cancer,free business increase the risk about eightfold (OR=8.18), and military increase the risk for fold(OR=4.09) while men deal with chemical material increase the risk about threefold (OR=2.5).In our study, the place of living was divided into three regions (South, North, and the center ofBasra) the risk of disease increases about threefold for both South and North of Basra comparewith the Centre of Basra. Cigarette smoking also increases the risk of twofold compare with nonsmokers